Harmonic Superfields in N=4 Supersymmetric Quantum Mechanics - Ivanov, E.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
This is a brief survey of applications of the harmonic superspace methods to the models of N=4 supersymmetric quantum mechanics (SQM). The main focus is on a recent progress in constructing SQM models with couplings to the background non-Abelian gauge fields. Besides reviewing and systemizing the relevant results, we present some new examples and make clarifying comments.